2010
DOI: 10.1080/14680629.2010.9690299
|View full text |Cite
|
Sign up to set email alerts
|

Damage Theory Applied to Flexural Fatigue Tests on Conventional and Asphalt Rubber Hot Mixes

Abstract: Application of the Continuum Damage Theory (CDT) to evaluate the evolution of internal damage in Hot Mix Asphalt (HMA) is investigated in this paper. The CDT leads to the formulation of a characteristic curve relating normalized pseudo-stiffness and the internal damage variable, and this curve is supposed to be unique for each material. The uniqueness of the characteristic curve was investigated in this paper by performing fatigue tests in which prismatic samples of HMA were subjected to cyclic bending loads u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…However, Daniel showed that damage can only accumulate during the tensile portion of the each cycle [4]. This assumption is also corroborated by the works of Underwood et al and Mello et al [6,24]. According to this assumption, in this study, only the tensile half of each cycle is used to determine pseudostrain.…”
Section: Damage Characterizationsupporting
confidence: 73%
See 1 more Smart Citation
“…However, Daniel showed that damage can only accumulate during the tensile portion of the each cycle [4]. This assumption is also corroborated by the works of Underwood et al and Mello et al [6,24]. According to this assumption, in this study, only the tensile half of each cycle is used to determine pseudostrain.…”
Section: Damage Characterizationsupporting
confidence: 73%
“…Since distribution of stress and strain within the prismatic specimen under flexural mode of loading is not uniform [24], for simplicity, only stress and strain value in the upper or lower portion of the bending beam's cross-section were used to develop continuum damage model. The on-specimen displacement measurement at the middle of the beam was utilized to calculate the maximum strain and stress at each loading cycle using Eqs.…”
Section: Damage Characterizationmentioning
confidence: 99%
“…However, an interaction between rubber particles and bitumen does exist [18] as well as a significant amount of rubber particles being dissolved into the bitumen by means of devulcanisation and depolymerisation [4,33]. It should also be noted that although the fatigue resistance and durability are improved by using higher binder content [34], using excessive binder content could lead to binder drain down and also impair the rutting resistance of the asphalt mixture [12,35].…”
Section: Introductionmentioning
confidence: 99%
“…However, fatigue failure of HMA is the most critical design criteria in flexible pavement and horizontal strain at the bottom of HMA under vehicle load is the key parameter to address this fatigue failure of flexible pavement [8,9]. Moreover, not only does vehicle load produce horizontal strain at the bottom of HMA, but also temperature variations at the bottom of HMA cause a horizontal strain.…”
Section: Introductionmentioning
confidence: 99%